1993
DOI: 10.1002/eqe.4290220604
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of material non‐linearities in steel structures subjected to transient dynamic loading

Abstract: SUMMARYThis paper is concerned with the modelling of the behaviour of steel under cyclic and dynamic loading conditions. After a general discussion regarding the requirements for accurate and efficient modelling in dynamics, two models are described and implemented. The bilinear stress-strain constitutive relationship with kinematic hardening is widely used in many computer codes, hence is used for 'control' purposes. The multisurface plasticity model is said to exhibit the important qualities of strain harden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The bilinear steel model with kinematic strain hardening was adopted for modelling the reinforcing steel. This follows earlier studies by Kateinas 28 and Elnashai and Izzuddin, 43 where it was indicated that the difference between bilinear representation and more refined models is not large.…”
Section: Program Models and Methodssupporting
confidence: 79%
“…The bilinear steel model with kinematic strain hardening was adopted for modelling the reinforcing steel. This follows earlier studies by Kateinas 28 and Elnashai and Izzuddin, 43 where it was indicated that the difference between bilinear representation and more refined models is not large.…”
Section: Program Models and Methodssupporting
confidence: 79%
“…In such cases, the tests were conducted using cyclic loading and pseudo-dynamic testing under earthquake strong-motion (e.g. Elnashai and Izzuddin [19]). At ÿrst, in this paper, we investigate maximum loads of steel piers.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…10 shows how the yield to ultimate tensile strength ratio varies as a function of the key solutes, carbon and manganese. A low ratio is essential in safe design against calamities such as earthquakes, because it is necessary then to sustain a lot of plasticity prior to fracture during dynamical loading [72,73].…”
Section: Expression Of Data and Control Algorithmsmentioning
confidence: 99%